GERAKAN SOSIAL DAN PERUBAHAN KEBIJAKAN PUBLIK Kasus Perlawanan Masyarakat Batak vs PT. Inti Indorayon Utama,di Porsea, Sumatera Utara - Dimpos Manulu (Populasi, 2007)
A case study which comprehensively elaborated the role of Porsea people movement and its surrounding to urge the present of government policy and decision series, considering with the establishment of PT. Inti Indorayon Utama in Porsea, Toba Samosir, North Sumatra. Data collecting was through literary works, institutional publishing, research documents, chronology, contact report and investigation, news clipping, letters, press release and statement, and last but not least was the participative observation and deep interview. Afterwards, the data was analyzed and interpreted with reference to social movement theories and their relationship with the public policy change. The finding of this research reveals that there has been no single factor or certain theoretical approach monopoly in explaining social movement comprehensively. The movement also has shown up two contributions all at once: trigging and influencing the government newly released policies and stimulating the company's new management to be more active in serving and developing the surrounding people. Both of these were possible to happen because of the people movement, without great expectancy to the complex and distortive state actors parliament and bureaucracy.